Status of Napoleon wrasse in Laamu Atoll, Maldives, after three decades of protection - P Roe; AS Hashim; V Evans; Y Sadovy de Mitcheson (Endangered Species Research, 2022)
The Napoleon or humphead wrasse Cheilinus undulatus is a large, globally threatened coral reef fish. In recognition of suspected declines and considering its ecotourism importance, the Maldives was the first country to ban its export in 1995. The present study, a quarter-century after the ban, documents the species around Laamu Atoll, southern Maldives, using dive guides and researchers to conduct surveys during commercial dive tourism trips. Data were collected on abundance, body size, and potential spawning sites in 4 habitat types: channels (reef passes to open ocean), inner reefs (reef slopes inside the atoll), outer reefs (reef slopes outside the atoll), and faros (isolated submerged reefs inside the atoll). Abundance was recorded in number of fish per hectare, and fish length was classified as <100 cm, ≥100 cm, or unknown size. Possible spawning aggregation sites were identified based on multiple occasions of temporarily increased fish density associated with large male presence. Mean densities ranged from 6.02 fish ha-1 in channels, 2.65 and 2.29 fish ha-1 in outer and inner reefs, respectively, and 0.73 fish ha-1 in faros. These densities are consistent with those found in unexploited areas in similar habitats elsewhere and indicate successful protection of the species on Laamu Atoll. The data highlight the significance of reef channel habitat for this species as important megafauna and the need for management to conserve both species and channel habitats. The value of non-specialist observers for conducting labour-intensive surveys on large, wide-ranging species is demonstrated.